THE FOOD AND FEEDING HABITS OF POLYNEMUS INDICUS (SHAW) - Karekar, P.S.; Bal, D.V. (Indian Journal of Fisheries, 2015)
A reference to the literature on the food and feeding habits of Polynemids shows that the information available is scanty. Mookerjee etat. (1946) observed that the food of Polynemus sextarius from Port Canning and Kolaghat consisted of algae, protozoa, Crustacea and fish. According to Chacko (1949) Eleutheronema tetradactylum and Polynemus heptadactylus are carnivores, feeding on prawns and fishes and actively predaceous in surface and midwaters. Bapat and Bal (1952) during their study of fish larvae have noted that young E. tetradactylum from Bombay waters feed on prawns, copepods, Squilla larvae and polychaetes. Malhotra (1953) has studied the food of juvenile, pre-adult and adult E. tetradactylum. Mohamed (1955) in his gross study of food of Polynemus indicus found that it feeds mainly on crustaceans but takes also fishes like Harpodon nehereus, Coilia dussumieri and small sciaenids.